A Unique International Polar Year Contribution: Lucien Turner, Capelin, and Climatic Change - Dunbar, M.J. (ARCTIC, 1983)
Lucien McShann Turner (1847-1909), one of the most able field naturalists in North America in his day, spent two years (1882-84) at Fort Chimo, Quebec, as meteorological observer for the U.S. Army Signal Service during the first International Polar Year. Among his many activities over and above his IPY duties was the collection and description of the fishes of the region. This paper reports on the significance of Turner's first record, in 1884, of the presence of the capelin (Malotus villosus) in very large numbers at the mouth of the Koksoak River. Mallotus is an excellent indicator of marine climate conditions, and the subsequent records of its presence and absence in Ungava Bay are reviewed in relation to climatic change in the North Atlantic-Subarctic region in general.Key words: capelin, Mallotus villosus, Ungava Bay, International Polar Year Lucien McShann Turner (1847-1909). l'un des meilleurs naturalistes sur le terrain en Amérique du Nord en son époque, passa deux ans à Fort-Chimo, au Québec, à titre d'observateur météorologique pour l'U.S. Army Signal Service au cours de la première Année polaire internationale (A.P.I.). En plus de ses devoirs découlant de l'A.P.I., il s'occupa à collectionner et à décrire les poissons de la région. Le présent article signale l'importance du premier rapport de Turner en 1884, portant sur la présence du capelin (Mallotus villosus) en grands nombres dans l'embouchure de la rivière Koksoak. Mallotus est un excellent indicateur de conditions climatiques marines, et les données signalant la présence ou l'absence du Mallotus dans la baie d'Ungava sont étudiées par rapport aux variations climatiques dans la région nord-atlantique-subarctique en général.Mots clés: capelin, Mallotus villosus, la baie d'Ungava, la première Année polaire internationale